PENGUATAN DISIPLIN SISWA MELALUI PEMBINAAN PERATURAN BARIS BERBARIS (PBB) PADA KEGIATAN EKTRAKURIKULER KETARUNAAN - Itang Enrico Pradana Mahardhika; Sumardjoko, Bambang; Fathoni, Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Disciplinary character education is one of the primary objectives in student development within schools, particularly through extracurricular activities. One activity considered effective in instilling disciplinary values is cadetship training through the Basic Marching Drill (PBB). This study aims to describe the strengthening of students' disciplinary character through PBB training in cadetship extracurricular activities at SMK Gula Rajawali, Madiun City. This research employs a qualitative approach with a case study design. The research subjects include cadetship extracurricular instructors and participating students. Data collection techniques were conducted through observation, interviews, and documentation. The results indicate that the PBB training is implemented in a structured and routine manner, emphasizing discipline in students' attitudes and behavior. The findings reveal a strengthening of disciplinary character, reflected in the improvement of students' independence, responsibility, and punctuality in both extracurricular and other school activities. Furthermore, PBB training fosters positive habits in adhering to regulations and executing tasks without direct supervision. In conclusion, PBB activities within cadetship extracurriculars play a vital role as a medium for sustainable disciplinary character building. This research is expected to serve as a reference for schools in developing character-based extracurricular programs.